Synthesis of the noveltype of pheny1 pyridinium compound as an antimicrobial agent - Jayatissa, T.B.R.N. (My University, 2010)
The continuing increase in the incidence of multi drug resistant pathogenic bacteria and shortage of new antimicrobial agents are the prime driver in efforts to identify novel antibacterial classes and it is a serious problem in treatment with infectious diseases. Therefore it is essential to synthesis novel compounds and evaluate the antimicrobial properties of the newly synthesis compounds. Pyridinium salts are used as an effective antimicrobial agent and various antimicrobialapplications in industrially and domestically for a long time. This work mainly focused on synthesis of pyridinium based salt and study of the in vitro interactionof aqueous solution of this compound with bacterial cells and to determine the cytotoxiceffect. In this experiment Staphylococcus aureus. Streptococcus species. Bacillus sublilis,Klebsiellaspecies and Escherichia coli bacterial cells were used as models to screen for antibacterialactivity. Theconvergencesynthesis of 4-phenylpyridine and a-(bromo )methylstyrene were carried out separatelyand finally combined to form 4-phenyl-I-(2-phenyl-allyl)-pyridinium bromide. This synthesis was carried out according to the previously published method. As a first step phenylmagnesiumbromide and N-methylforrnylpyridinium chloride were prepared and then combined to yield 4-phenyl-N-methylformyldihydropyridine. Then the compound was hydrolyzedusing a 10% ammonium chloride solution. Then it was rearomatized to 4- phenylpyridineby potassium permanganate. Then it was precipitated as the hydrochloride salt in ethanolmedium. Then the isolated product was basified and the resulting phenyl pyridine was later recrystallized using ethanol/diethylether solvent system. As a second step allylic brominationof a-methyl styrene was achieved and later the product (a-(bromo)methylstyrene) wasisolatedby column chromatography and TLC (Thin layer chromatography). Finally the combinationreaction of phenylpyridine and a-(bromo )methylstyrene was carried out to obtain 4- phenyl-I-(2-phenyl-allyl)-pyridinium bromide. Then the isolated product was recrstallised using theethanol/diethylethersolvent system. Thenthe investigationwas undertaken to assess antimicrobial properties of this pyridinium based saltin orderto establish the possibility of this compound as an antimicrobial agent. Initially evaluatethe susceptibility of this compound against above mentioned bacterial strains in vitro usingdisk diffusion method. According to the antimicrobial test results strong inhibitory effect wasobservedon Staphylococcus aureus (larger inhibition zone was formed) and Escherichia coli showedvery small sensitivity (very small inhibition zone) towards the 4-phenyl-l-(2- phenyl-allyl)-pyridinium bromide while all the other tested bacterial strains (Streptococcus sp, Bacillussubtilis,Klebsiella sp) revealed resistant against the compound. Staphylococcus aureus was selected to determine the MIC (Minimum Inhibitory Concentration) b) thedisk diffusion method because it was exhibited larger inhibition zone for the pyridinium salt. It was done by as preparing five fold dilutions of 4-phenyl-I-(2-phenyl-allyl)-pyridinium bromidesalt in water and introduced this series to the petriplates containing equal amount of bacteriallawns using 6 mm paper disk. The MIC of this salt for Staphylococcus aureus is ::;20 ~g/ml. Modeof interaction and the exact mechanism of binding of this compound to the bacterial cells arestill not understood, according to the previous studies it can be suggested that quaternary pyridinium type compounds and compounds having pyridinium moiety mainly effects on bacterialcell walls. And also it can be supposed that different sensitivities of bacterial strains towardsthe compound mainly due to their cell wall differences. Finally comparison of antibacterial activity of 4-phenyl- I-(2-phenyl-allyl)-pyridinium bromide with four other antibiotics (penicillin, Cloxacillin, Erythromycin and Vancomycin) which are givento cure staphylococcus aureus infections was carried out using disk diffusion method.